1995
DOI: 10.1038/sc.1995.46
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathies in the upper extremities of paraplegic wheelchair marathon racers

Abstract: In order to know if peripheral neuropathies in the upper extremities of paraplegic individuals are induced by participating in wheelchair marathon races, we performed nerve conduction studies bilaterally on the median, ulnar, and radial nerves of 10 male wheelchair marathon racers, and on 10 male sedentary paraplegic individuals. In five of 10 paraplegic racers, and in nine of 10 sedentary paraplegics there was a decrease of motor nerve conduction velocities and/or prolongation of motor or sensory nerve distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
0
10
0
5
Order By: Relevance
“…Another study indicated prevalence of CTS of approximately 50% in wheelchair racers [21]. Dozono et al [22] reported similar prevalence of CTS in wheelchair marathon racers and other patients on wheelchair, which is approximately 10%. Likewise, our study findings also showed that the prevalence of CTS in WCB players and other paraplegic patients were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated prevalence of CTS of approximately 50% in wheelchair racers [21]. Dozono et al [22] reported similar prevalence of CTS in wheelchair marathon racers and other patients on wheelchair, which is approximately 10%. Likewise, our study findings also showed that the prevalence of CTS in WCB players and other paraplegic patients were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in technique and definition of peripheral neuropathy are the most likely explanations for the discrepancy of prevalences in these two studies. Further, Dozono et al 20 found that 50% of WC road racers had peripheral neuropathy based on NCSs, but none had subjective complaints consistent with peripheral neuropathy. Thus, the limited available literature is still somewhat inconclusive.…”
Section: Etiologymentioning
confidence: 99%
“…Similarly, Jackson et al 19 reported that although only 30% of WC basketball players had symptoms of carpal tunnel syndrome (CTS), 52% had electrodiagnostic evidence of median neuropathy. Dozono et al 20 reported a 90% prevalence of peripheral neuropathies diagnosed by nerve conduction studies (NCSs), with the ulnar and radial nerves being most commonly affected in the WC nonathletes studied. Differences in technique and definition of peripheral neuropathy are the most likely explanations for the discrepancy of prevalences in these two studies.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations